2010
DOI: 10.1007/s00468-010-0414-0
|View full text |Cite
|
Sign up to set email alerts
|

Vessel features of Quercus ilex L. growing under Mediterranean climate have a better climatic signal than tree-ring width

Abstract: We investigated whether vessel time series of Holm oak (Quercus ilex L.), a diffuse to semi-ring-porous species, can record a climatic signal which differs from the signal encoded in tree-ring width (TRW). The study was conducted in ten Q. ilex trees from a coppice stand in northeast Spain. Chronologies of TRW, mean vessel area (MVA) and maximum vessel area (MAX) were developed and correlated with climate data, for the period 1985-2004 (20 years). Our results indicate that vessel features contain environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 45 publications
11
52
2
1
Order By: Relevance
“…Moreover, these values are consistent with what can be found for other tree species of the Mediterranean area (e.g. Campelo et al, 2007;Campelo et al, 2010;Cherubini et al, 2003;Garfì, 1997;Lebourgeois et al, 2012;Touchan et al, 2014).…”
Section: Complacence and Sensitivity Towards Climatesupporting
confidence: 91%
“…Moreover, these values are consistent with what can be found for other tree species of the Mediterranean area (e.g. Campelo et al, 2007;Campelo et al, 2010;Cherubini et al, 2003;Garfì, 1997;Lebourgeois et al, 2012;Touchan et al, 2014).…”
Section: Complacence and Sensitivity Towards Climatesupporting
confidence: 91%
“…In this study, the overall frequency distribution of vessel was left-skewed, as previously reported for Q. faginea (Villar-Salvador et al 1997, Corcuera et al 2004a, Alla & Camarero 2012, Q. robur and Q. ilex (García-González & Eckstein 2003, Campelo et al 2010, Corcuera et al 2004b). The vessel distribution seems age-related, and the …”
Section: Discussionsupporting
confidence: 77%
“…(Figure 1). It is located in the northern part of Gafurov district in Sogd Province, Tajikistan with temperate climate zone [35][36][37]. Since in Taboshar the uranium mining industry was set up by USSR in the late 1940s and early 1950s as a part of the nuclear weapon program, the research area under investigation is probably impacted by remnants of nuclear weapons production.…”
Section: Physical Settingsmentioning
confidence: 99%